Circ-SHPRH in human cancers: a systematic review and meta-analysis - Xiong, Hong; Huang, Gaozhen; Zhu, Yi; Chen, Ruiqi; Zuo, Ling; Liu, Hongwei (Frontiers in Cell and Developmental Biology, 2023)
Circular RNA (circRNA) molecules are noncoding RNAs with ring-like structures formed by co-valent bonds and are characterized by no 5’ cap or polyadenylated tails. Increasing evidence shows that circRNAs may play an important role in tumorigenesis and cancer metastasis. Circ-SHPRH is a circRNA that is closely associated with human cancers, such as lung cancer, bladder cancer, liver cancer, colorectal cancer, glioma cancer, and cholangiocarcinoma, and it originates from exons 26-29 of the SHPRH gene. Many studies have shown that circ-SHPRH acts as a miRNA sponge or regulatory protein that regulates downstream genes or signal pathways, and exerts specific biological functions that affect the proliferation, invasion, and apoptosis of cancer cells. Circ-SHPRH also has the potential to be a novel biomarker to improve our under-standing of the mechanisms of circRNA in cancer progression and development. Therefore, this review will help enrich our understanding of the role of circRNAs in cancer by summarizing the potential value and application of circ-SHPRH in cancer diagnosis and treatment.